Which combined nerve conduction study scores are best suited for polyneuropathy in diabetic patients?. Issue 2 (5th November 2021) - Dunker, Øystein; Nilsen, Kristian Bernhard; Olsen, Sandra Elise; Åsvold, Bjørn Olav; Bjørgaas, Marit Ragnhild Rokne; Sand, Trond
Abstract: Introduction/Aims: Nerve conduction studies (NCS) are widely used in diagnosing diabetic polyneuropathy. Combining the Z scores of several measures (Z‐compounds) may improve diagnostics by grading abnormality. We aimed to determine which combination of nerves and measures is best suited for studies of diabetic polyneuropathy. Methods: Sixty‐eight patients with type 1 diabetes and 35 controls were included in this study. NCS measurements were taken from commonly investigated nerves in one arm and both legs. Different Z‐compounds were calculated and compared with reference material to assess abnormality. A sensitivity proxy, the accuracy index (AI), and Cohen's d were calculated. Results: Z‐compounds with the highest AI consisted of the tibial and peroneal motor, and the sural, superficial peroneal, and tibial medial plantar sensory nerves in one or two legs. All Z‐compounds were able to discriminate between diabetic subjects and nondiabetic controls (mean Cohen's d = 1.42 [range, 1.03‐1.63]). The association between AI and number of measures was best explained logarithmically (R 2 = 0.401), with diminishing returns above approximately 14 or 15 measures. F‐wave inclusion may increase the AI of the Z compounds. Although often clinically useful among the non‐elderly, the additional inclusion of medial plantar NCS into Z‐compounds in general did not improve AI. Discussion: Performing unilateral NCS in several motor and sensory lower extremity nerves is suited for the evaluation of polyneuropathy in diabetic patients. The use of Z‐compounds may improve diagnostic accuracy in diabetic polyneuropathy and may be particularly useful for follow‐up research studies as single summary measures of NCS abnormality development over time. Abstract : A Z‐compound consisting of five unilateral lower extremity nerves is well suited for evaluating polyneuropathy in diabetic patients. see Editorial on pages 135–136 in this issue